Worst case scenario : a novel - Newman, T. J. (Novelist) (Little, Brown and Company, 2024)
"When a pilot suffers a heart attack at 35,000 feet, a commercial airliner filled with passengers crashes into a nuclear power plant in the small town of Waketa, Minnesota, which becomes ground zero for a catastrophic national crisis with global implications. Ordinary people--power plant employees, firefighters, teachers, families, neighbors, and friends--are thrust into an extraordinary situation as they face the ultimate test of their lives. It will take the combined courage, ingenuity, and determination of a brave few to save not only their community and loved ones, but the fate of humanity at large."--